Study on Optical Fiber Pressure Sensors with Temperature-Insensitivity Based on Fabry-Perot Interferometry - Lai, Chih-Wei; Yur, Jiahn-Piring; Liao, Chia-Chi; Lo, Yu-Lung (Recent Patents on Signal Processing (Discontinued), 2011)
This paper presents the fiber pressure sensor with temperature-insensitivity based on the principle of Fabry- Perot interferometry. The design and fabrication of the sensor are based on Micro Electro-Mechanical Systems (MEMS) technique and only need a few simple procedures. The pressure sensing membrane consists of a polyimide layer, a metal reflective layer, and a SU_8 layer covered on the metal layer. Also, the fiber end facet is coated another SU_8 layer for temperature compensation. The thicknesses of temperature compensator and pressure membrane are analyzed by Finite Element Method (FEM) model. This optical fiber pressure sensor exhibits an approximately linear response to applied pressure ranging from 0 to 60 kPa under the temperature difference about 100°C. The simple fabrication, small size, linear response, and temperature-insensitivity make the sensor suitable for many industrial applications. Therefore, several researches and patents introduce various optical fiber Fabry-Perot pressure sensors which are designed and improved in practical applications.
Keywords: light interferometry